Coherent and emotional. - Muhammad Hafidz Mohd Senor. (2012)
In his 1936 essay Der Erzähler (The Storyteller), Walter Benjamin laments the decline of storytelling, attributing it to a societal shift in the value of experience. In our age where one has instant access to information, can photography recapture the "ability to exchange experiences". In search of a new artistic vigour, Hafidz Senor documents his encounters with visionary figures who produce harmonies of "the soul, the eye, and the hand". These exchanges resulted in a poetic binary that is tense and calm, clear and ambiguous, coherent and emotional. Working in a period where photography surrenders itself to the cerebral, often expected to present a clear artistic and creative process, the photographer takes the viewer on a journey and pushes one to reflect and question the value of experience.